College students' readiness in learning Mandarin language as second language: a case study of Kolej Profesional MARA Beranang - Jafri, Nuraini; Abdul Manaf, Umi Kalthom (Faculty of Educational Studies, Universiti Putra Malaysia, 2017)
This is a case study of Kolej Profesional MARA (KPM) Beranang students’ readiness in learning Mandarin language as a second language (L2). The programme started more than four years ago and there have been some concerns on students’ readiness in learning this language as L2. The ‘silent stage’ mode that can be felt during the teaching and learning processes and the reluctance of students in conversing the language are the main issues. Therefore, this concept paper proposed to study students’ readiness in learning Mandarin language as L2 in KPM Beranang. The research questions that will be used to answer the objectives are 1) what is the level of college students’ readiness for learning Mandarin language as L2?, 2) what is the level of oral efficiency of college students in their readiness for learning Mandarin language as L2?, and 3) what is the level of listening comprehension of college students in their readiness for learning Mandarin language as L2?. This research will be conducted qualitatively using the data received from observation, focus group interviews and document analysis. It is hoped that the findings of this study will provide comprehensive insights towards the review of the curriculum for the betterment of the students at KPM Beranang in learning Mandarin as an L2.